Seasonal Variation of Indigenous Saccharomyces cerevisiae Strains Isolated from Vineyards of the Western Cape in South Africa - van der Westhuizen, T.J.; Augustyn, O.P.H.; Khan, W.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
There is strong support for the use of naturally-occurring Saccharomyces cerevisiae strains that improve the sensory quality of wines and reflect the characteristics of a given region. Contrary to popular belief, S. cerevisiae is found at very low numbers on healthy, undamaged grapes and is rarely isolated from intact berries. The majority of studies on the population kinetics and geographic distribution of indigenous S. cerevisiae strains have not adequately focused on the variation in their numbers over a longer period of time. This paper discusses the results obtained in the first phase of a comprehensive research programme aimed at assessing how the natural population dynamics of S. cerevisiae are affected over the long term by abiotic factors. Indigenous strains of S. cerevisiae were aseptically isolated from eight sites in four areas in the coastal regions of the Western Cape, South Africa, during 1995 through 1998. Thirty colonies per site were isolated and the S. cerevisiae strains were characterised by electrophoretic karyotyping. Strain numbers per site varied over the four-year study period. Weather conditions resulting in severe fungal infestations and heavy applications of chemical sprays dramatically reduced the numbers of S. cerevisiae strains recovered during 1997. A return to normal weather patterns in 1998 resulted in a gradual recovery of the indigenous population. Indications are that some of the strains isolated are widespread in the study area and may represent yeasts typical of the area. Commercial wine yeast strains were recovered in only a few instances and the likelihood that commercial yeasts will eventually replace the natural yeast microflora in vineyards seems remote.